Implementasi Konsep Addiction in Catchiness pada Perancangan Interior “Rumah Cokelat” di Surabaya - Jeanny Florencia Halim (Intra, 2016)
Chocolate is one of the most special cocoa products compared to other products. Chocolate contains flavanol compounds that function to soothe the nerves. This chocolate’s compound is what people need, especially in Surabaya. Most people in Surabaya are experiencing stress, discomfort, and other problems due to the activities and conditions of congested city. So that chocolate has the potential to be appreciated as a place where people can be recreation, relaxation, get information and share their creativity by utilizing chocolate as the basic idea of making the place’s design. Interior Design "Chocolate House" in Surabaya will be a recreation place as well as the new icon of Surabaya where people are able to relaxation, experience new things, get some knowledge, and also as a form of appreciation towards the chocolate itself. The concept used is taking the characteristic of the chocolate itself, adapted with the needs and desires of the community. Chocolate has properties that make people become addicted, so that’s why the interior design "Chocolate House" raises the concept of Addiction In Catchiness. This concept gives impression to the people who come, both in terms of interior and knowledge, causing addiction to come again. The character of chocolate applied on shapes, colors, atmosphere inside the room. This design maximizes the potential of chocolate in each facility and design, so that for those who enters the room can feel and understand that chocolate has many benefits they were never thought before.